THE ROLE OF FICTION IN IMPROVING THE INTELLECTUAL POTENTIAL OF STUDENTS - Rakhmonova Dilfuza Makhmudovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
the article provides general information about the factors affecting the intellectual development of schoolchildren. At the same time, the role of fiction in the intellectual development of schoolchildren is explained in detail, important factors in the development of knowledge potential are listed.